Increasing Complexity of Cryptographic Using Combination of Hill Cipher and Cipher Block Chaining - Abd Charis Fauzan; Veradella Yuelisa Mafula (Journal of Development Research, 2020)
Security and confidentiality of documents stored on a computer is an important aspect in the field of computer or information system security. Documents will no longer be useful if they are intercepted or hijacked by unauthorized people, they will even endanger the document owner, if documents containing important information are misused by irresponsible people. Therefore the documents on the computer must be preserved so that they are only accepted and used by interested persons. One of the solutions to prevent eavesdropping of documents is to use cryptography. This study aims to increase cryptographic complexity using a combination of hill cipher algorithms and block chaining cipher modes. The combination of the two methods is expected to be able to cover the shortcomings of each method so that the cryptographic complexity can be increased. The method in this study consists of two stages, namely the document encryption and document decryption stages. The encryption stage is to change the plaintext document into a ciphertext document, on the other hand, the decryption stage is to change the ciphertext document back into a plaintext document. The stages for document encryption include; 1) retrieve plain text messages in the document so that they can be processed by the system (parsing); 2) encryption to convert plaintext documents into ciphertext documents using the hill cipher algorithm; 3) encryption to convert plaintext documents into cipher text documents using cipher block chaining mode. While the methods for decryption are 1) taking the ciphertext message in the document so that it can be processed by the system (parsing); 2) decryption to convert ciphertext documents into plaintext documents using cipher block chaining mode; 3) decryption to convert ciphertext documents into plaintext documents using a hill cipher.